Perkembangan dan Faktor yang Mempengaruhi Munculnya Permukiman Kumuh di Kelurahan Tegalsari Kota Tegal (Tahun 2007-2017) - Sabila, Timami; Sriyono, Sriyono (Geo-Image, 2019)
Tegalsari is a coastal area of Tegal City and has a high slum area in Tegal City, which is 31.43 Ha. In its growth, slums in Tegalsari Village occurred due to compaction, aging, and inudation processes. This study aims to: (1) Know the growth of the spread of slums in Tegalsari Village in 2007-2017. (2) Knowing the factors that influence the emergence of slums in Tegalsari Village. This research is located in several RW located in Tegalsari Village, Tegal City, namely RW 01, 02, 03, 09, and 03A. The data analysis technique used is descriptive analysis and spatial process analysis. The results showed that the growth process of slums in RW 01.02.02.03 and 03A was centripetal spatial growth horizontally. which means the process of adding buildings that occur in the inner city and in the research area is included in the process of filling spaces on vacant land by building houses to be used as dwellings. While the factors that influence slum licensing in the study area are economic factors, disaster factors (flood tide), and psychological factors (comfort and feeling of security).